Analysis of Harmonization of Professional Standards in the System of Higher QualifiedStaff Training - Svetlana M. Bychkova; Svetlana A. Timoshenko (Учёт. Анализ. Аудит)
Topic. Nowadays the requirements to the quality of educational services are really high. They must provide the training of effective workers who are in demand in labor markets. Higher educational institutions must train a competent specialist competitive in the labor market. Purpose. Making a multipurpose authors’ research of the modern state of highly qualified staff training, taking into account the application of professional standards, and also identifying positive and negative trends in the process of conjunction the training in question with professional standards. Methodology. The study is made by means of the system analysis. The retrospective analysis of development of the Russian higher education system is also applied. Results. The authorial structure of staff potential in a higher education institution with the description of its components is developed. The comparison of levels of professional qualifications, levels of education and positions of faculty is made which showed the high variability in qualifying levels and also certain coincidence in qualification and education description of hierarchically different positions. Conclusions. The conclusions confirm the need to improve the existing system of the higher education in a number of the directions. It is necessary to understand that the academic and research staff potential is the multidimensional category the contents of which is more complicated than the staff capacity of the organization.